Prevalence and determinants of school bullying in Qatar: a cross-sectional study - Madeeha Kamal; Samer Ali; Kholoud Mohamed; Aamir Kareem; Suzan M. Kirdi; Mai Hani; Manasik Hassan; Schahla Al-Shibli; Prem Chandra (BMC, 2023)
Abstract Background School bullying is a wide-spread phenomenon that manifests in various forms. It has both short-term and long-term devastating consequences on physical, mental and social wellbeing. The Middle East and North Africa (MENA) region, including Qatar, has a relatively high prevalence of school bullying. This research aims at identifying the prevalence of bullying, particularly unsafe environments were bullying takes place, and its attributes at schools in Qatar. Methods In a cross-sectional study, 980 students from 10 schools in Qatar completed an anonymous self-completion standardized questionnaire to assess the different aspects of bullying from school students' point of view. Results The prevalence of bullying victimization and perpetration was found to be 41.0% and 31.7% among school students in Qatar, respectively. Classroom (67.5%) and hallways (64.8%) were the most frequently indicated environments of bullying whereas library was the least indicated one (28.3%). Verbal bullying was the most used type of bullying by students. Overall, students in Qatar believe that bullying is considerably a significant issue at their schools, yet schools are safe place for them to be in. Gender, age, ethnicity, school grade and years living in Qatar showed significant differences among the students. Conclusion School bullying is a serious, yet a manageable global problem. Our findings re-demonstrated the alarming high prevalence of school bullying in Qatar, highlighted student related and school related factors which have implications for future multidimensional action and research and recommended measures to foster safety at school.